对气候变暖问题争议的分析 - 王绍武; 龚道溢 (地理研究, 2001)
综合评述和分析了近年来关于全球气候变暖问题的研究。重点是有关气候变暖的一些争议。目前的结论是：（1）19世纪中期以来全球平均地表气温上升了0.4～0.8℃；（2）全球气候变暖的论断得到了海洋温度、大气温度、钻孔温度、陆地雪盖、海冰及冰川资料的支持；（3）1998年是近一个半世纪有观测资料以来最暖的一年，对1961～1990年平均的距平为0.55℃。20世纪变暖的趋势为0.066℃/10a；（4）1990′s是20世纪最暖的10年，平均气温距平0.35℃，也可能是500a 或者甚至1000a来最暖的10年。所以，20世纪气候的变暖是无可怀疑的。人类活动影响很可能是20世纪气候变暖的主要原因，至少是主要原因之一。 Some problems in the global climate studies are discussed in this manuscript. Special attention was given to the debates on global warming. Although it is widely accepted that the anthropologic greenhouse effect would be responsible for the recent global warming, there are always unceasing skepticism. Numerous evidences show that it is indubitable on the climate warming itself. The global surface air temperature has increased by 0.4-0.8(C since the mid 19th century. Substantial changes associated with the climatic warming also occurred during the past century. These related transformations have been observed in the ocean temperature, atmospheric temperature, reconstructed temperatures from the evaluation of mountain snowlines and borehole thermometry, land snow cover, sea ice cover and the mountanious glaciers. It is found that 1998 is the warmest year on records during the past 150 years. Global averaged annual temperature in 1998 is 0.55(C above the mean of 1961-90. The linear warming trend for the 20th century is 0.066(C/10a. The 1990s (with the anomaly of +0.35(C) is the warmest decade not only in the 20 century but also in the past 500years and maybe even in the last millennium. After all, the global warming in the 20th century is an explicit fact, whereas there are doubts on which factor should be responsible for it. Anthropologic factor may be the most important reason, at least, may be one of the most important factors if there are some other crucial causes. To some degree, the sciences of climate change benefit from the debates on the global warming , since there are increasing concerns and demands for a better understanding of the climate system (including their natural variability and their interaction with the human-induced greenhouse effects). Unfortunately, the debates and some related conclusions are no more 'pure' scientific questions, but political affairs. 国家重点基础研究发展计划(973计划); 国家自然科学基金 中文核心期刊要目总览(PKU) 中国科学引文数据库(CSCD) 0 2 153-160 20